A Survey on knowledge extraction Approaches from Big Data and Rectifying Misclassification strategies - Arora, Jyoti; Sood, Ambica (International Journal of Computer Sciences and Engineering, 2025)
The amount of data is increasing now a days due to usage of portable resources like smart phones, tablets and many more for accessing social sites. The requirement to analyze such big data to extract meaningful data came into existence. Traditional methods have been explored by number of researchers to analyze such data. These methods removed faulty data, uncertain data or misclassified data for better analyses. But this leads to loss of data. There is need to take into consideration the rectification of uncertainty in aspect of big datasets also. So, In this paper we survey big data, some traditional methods for data analyses, advance methods for data analyses, issues related to these methods, misclassification concept, the survey of rectification techniques for high accuracy followed by bearer future scope.